The quiet man - Wayne, John, 1907-1979.; O'Hara, Maureen, 1920-; Fitzgerald, Barry, 1888-1961.; Bond, Ward, 1903-1960.; McLaglen, Victor, 1886-1959.; Ford, John, 1894-1973.; Cooper, Merian C.; Nugent, Frank S.; Maltin, Leonard; Republic Pictures Home Video (Firm); Artisan Entertainment (Firm); Republic Pictures Corporation; et al. (Los Angeles : Republic Pictures Home Video : Distributed by Artisan Entertainment, 1999)
Sean Thornton, an American prizefighter who swears off boxing after accidentally killing an opponent, returns to the Irish town of his birth, and finds happiness when he falls in love with, and marries the fiery Mary Kate. Though tempted to pick up the gloves against Mary Kate's brother, the town bully.
Originally produced as a motion picture in 1952.
Includes "The making of The quiet man" documentary, hosted by Leonard Maltin.
Director of photography, Winton C. Hoch ; editor, Jack Murray ; music by Vic Young.
John Wayne, Maureen O'Hara, Barry Fitzgerald, Ward Bond, Victor McLaglen.
Not rated by the MPAA.
DVD; Dolby digital mono.
Keywords: Man-woman relationships -- Ireland -- Drama; Video recordings for the hearing impaired; Ireland -- Social life and customs -- Drama; Videodiscs; Feature films; Love stories; Comedy films